2022
DOI: 10.3390/rs14143396
|View full text |Cite
|
Sign up to set email alerts
|

Comparing CNNs and Random Forests for Landsat Image Segmentation Trained on a Large Proxy Land Cover Dataset

Abstract: Land cover mapping from satellite images has progressed from visual and statistical approaches to Random Forests (RFs) and, more recently, advanced image recognition techniques such as convolutional neural networks (CNNs). CNNs have a conceptual benefit over RFs in recognising spatial feature context, but potentially at the cost of reduced spatial detail. We tested the use of CNNs for improved land cover mapping based on Landsat data, compared with RFs, for a study area of approximately 500 km × 500 km in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Although the application of CNNs to land cover classification could have higher computing-power demands and may require additional region-specific calibration of ground-truth data [e.g. mentioned in ( 60 , 61 )], these additional challenges could be solved by introducing additional instruments such as hyperparameter tuning and model pre-training. Therefore, using CNNs to classify land cover has large potential for future research to investigate regional or even subregional economic activity at a global scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although the application of CNNs to land cover classification could have higher computing-power demands and may require additional region-specific calibration of ground-truth data [e.g. mentioned in ( 60 , 61 )], these additional challenges could be solved by introducing additional instruments such as hyperparameter tuning and model pre-training. Therefore, using CNNs to classify land cover has large potential for future research to investigate regional or even subregional economic activity at a global scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…By 2023, the importance of Band 4 in chlorophyll absorption remained critical for vegetation health identification; Band 2 was pivotal in providing textural details due to its moisture and shadow sensitivity, and Band 1 was essential for atmospheric corrections to improve forest health assessments. This expanding understanding is vital for establishing adaptive forest management techniques that respond to changing climatic circumstances and enable sustainable water resource management in geothermal fields, thus improving conservation efforts and maintaining ecological balance [101,102].…”
Section: Feature Importancementioning
confidence: 99%
“…Meanwhile, U-Net [21] was based on the encoder-decoder structure and was proposed to handle medical image segmentation tasks. It is the most widely used deep learning architecture for remote sensing image segmentation and has achieved satisfactory results [30]. In order to better extract the feature information of NIR band of satellite imagery, inspired by U-Net, we proposed a high-resolution forest remote sensing image segmentation network by fusing multi-scale features based on double input.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Wei et al [29] demonstrated that the CNN-based image segmentation network achieved much better results than the spectral vegetation index-based method and the machine-learning-based method in the task of mapping the large plateau forest of Sanjiangyuan. Among the prevalent deep learning image segmentation networks, U-Net, which is designed based on the encoder-decoder structure, is the most commonly used deep learning architecture to perform remote sensing image segmentation [30]. In the field of forest remote sensing image segmentation, Freudenberg et al [31] developed a novel method for detecting oil palm plantations using very high-resolution satellite imagery, based on the U-Net architecture.…”
Section: Introductionmentioning
confidence: 99%